Evaluating the Validity and Reliability of the Persian Version of the Cyber-Relationship Motives Questionnaire - Isanejad, Omid; Mohamadi, Asrin (Journal of Assessment and Research in Applied Counseling (JARAC), 2026)
Objective: This study aimed to evaluate the validity and reliability of the Persian version of the Cyber-Relationship Motives (CRM) questionnaire among Iranian university students.Methods and Materials: A total of 475 students from the University of Kurdistan (70.5% female; mean age = 22, SD = 3) completed the CRM and the Internet Affective Relationships Inventory (IARI). The CRM was translated into Persian using a forward–backward translation method, reviewed by expert committees, and refined through iterative revisions. Data collection employed paper-based surveys, and 100 additional participants with internet access but no preference for online social interactions were included for discriminant validity testing. Structural validity was examined via confirmatory factor analysis (CFA) using AMOS-25, with model fit assessed through indices including CMIN/df, AGFI, GFI, CFI, PNFI, TLI, and RMSEA. Internal consistency was evaluated using Cronbach’s alpha, test–retest reliability through Pearson correlation, and convergent and concurrent validity via correlations with IARI.Findings: CFA confirmed the nine-factor structure of the CRM, showing acceptable fit indices (CMIN/df = 2.741; CFI = 0.92; TLI = 0.91; RMSEA = 0.061). Cronbach’s alpha coefficients ranged from 0.47 to 0.97 across subscales, with the overall scale α = 0.92, indicating good internal consistency. Test–retest reliability over one month ranged from r = 0.71 to r = 0.92 (p < 0.01). Significant positive correlations were found between CRM subscales and IARI dimensions, supporting convergent validity. Discriminant validity testing revealed that participants preferring online interactions scored significantly higher on adventure, escape to a virtual world, and romance dimensions (p < 0.01). Gender differences emerged in the romance dimension, with men scoring higher than women, particularly in the “finding a sexual partner” subscale.Conclusion: The Persian version of the CRM questionnaire demonstrated robust psychometric properties, confirming its validity and reliability for assessing motives behind cyber-relationships in Iranian contexts. Its stable factor structure, strong internal consistency, and meaningful correlations with related constructs support its applicability for future research and practical assessments in both academic and counseling settings.